Preserving health - Gerževič, Mitja (Kinesiologia Slovenica, 2025)
Introduction: The aim of this study was to evaluate the motives and attitudes of the Nursing Home residents for exercising in Senior Exercise Park (SEP). Methods: Fifty volunteers (79.3 ± 8.4 years; 80% women; 50% exercising in SEP) were interviewed. Beside the descriptive statistics, a one-sample t-test and a chi-square test were used. Results: The results showed that physical activity (PA) performed by the respondents in the past was not significantly (p>0.05) related to their engagement in the SEP. More than a half of those who had been exercising in the SEP were exercising five or more times per week, which was also significantly (p<0.05) more frequent than the recommended three times per week. The majority of those who exercised in the SEP spent up to 30 minutes for each exercise session. The most frequent motives for exercising in the SEP were medical/health factors, challenge/benefit and curiosity. Among the reasons why some Nursing Home residents had not engaged in the SEP exercise, the most frequently mentioned were health problems, physical difficulties and lack of interest. The main benefit of the SEP exercise was the ability to perform everyday tasks much easier, feeling better and being in a better mood. Discussion and Conclusions: Installation of SEPs in the Nursing Homes is reasonable and could represent an important home’s achievement, as it can significantly contribute to the increase in PA of its residents. Moreover, it can also have an indirect positive effect on their health and overall home\'s atmosphere.
Keywords: attitudes; elderly,; motives; motivi; outdoor exercise; physical activity; stališča; starostniki; telesna aktivnost; vadba na prostem